2022
DOI: 10.3390/ijerph191811357
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficacy and Safety of Different Pterygium Surgeries: A Review of the Literature

Abstract: The search for the “gold standard” in the surgical treatment of pterygium has been ongoing for over two decades. Despite the development of various surgical techniques, recurrence rates range from 6.7% to 88% depending on the method used. This review discusses the latest and most commonly used methods for the surgical removal of pterygium, primarily focusing on efficacy and safety. Moreover, this review includes articles that either evaluated or compared surgical methods and clinical trials for primary and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Management of pterygium is surgical, and a wide range of techniques have been described: bare sclera, conjunctival flap, conjunctival autograft, limbal conjunctival autograft, and amniotic membrane. Adjuvant therapies for pterygium management have also been used, such as mitomycin C, beta-radiation, 5-fluorouracil (5-FU), topical use of bevacizumab, and interferons [ 46 ]. The goal of surgery is to excise the pterygium, restore the cornea surface, and prevent the risk of pterygium recurrence.…”
Section: Corneal Limbusmentioning
confidence: 99%
See 2 more Smart Citations
“…Management of pterygium is surgical, and a wide range of techniques have been described: bare sclera, conjunctival flap, conjunctival autograft, limbal conjunctival autograft, and amniotic membrane. Adjuvant therapies for pterygium management have also been used, such as mitomycin C, beta-radiation, 5-fluorouracil (5-FU), topical use of bevacizumab, and interferons [ 46 ]. The goal of surgery is to excise the pterygium, restore the cornea surface, and prevent the risk of pterygium recurrence.…”
Section: Corneal Limbusmentioning
confidence: 99%
“…The conjunctival autologous graft (CAG) consists in covering the bare sclera with a free graft of autologous conjunctiva after the pterygium removal, and it is nowadays the preferred approach given lower incidence of recurrence, usually between 3.3% and 16.7% in the case of primary pterygium [ 49 ], and around 33% in the case of treatment of pterygium recurrence [ 50 ]. The free autograft can be fixated with sutures (commonly Vicryl 8/0), fibrin glue, or the patient’s autologous blood [ 46 , 51 ]. No significant differences in pterygium recurrence among these three techniques are reported in the literature according to meta-analysis, however, the conjunctival autograft with fibrin glue presents a lower risk of graft displacement and conjunctival retraction, and also a shorter surgery time, compared to the other two techniques [ 52 , 53 ].…”
Section: Corneal Limbusmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, surgical resection is the only effective treatment for pterygium [2] , which mainly includes scleral exposure, conjunctiva-ap transposition, conjunctival autografting, and amniotic membrane transplantation [3][4] . Numerous clinical studies have shown that treatment by conjunctival autografting has the lowest recurrence rate among these surgical treatments, and thus conjunctival autografting has been recommended as the preferred treatment for primary pterygium [5][6] . However, the surgical injuries could lead to substantial ocular surface in ammation, causing evident ocular irritation in the patients post-surgery [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Fibrin glue is used due to its various advantages such as easy fixation of the graft, shorter operation time, reduction in complications and postoperative discomfort. However, high cost of the glue, risk of transmission of infections and severe allergic reactions are its main disadvantage 4 .…”
Section: Introductionmentioning
confidence: 99%